Analysis of glutathione and vitamin C effects. (2006) - Pitarque, M.; Creus, A.; Marcos, R.
Abstract : The alkaline single-cell gel electrophoresis (or Comet) assay was applied to evaluate the eventual DNA damage induced by the triphenolic metabolite of benzene, 1, 2, 4-benzenetriol (BT), in isolated human lymphocytes. Prior to BT treatment, ranging from 5 to 50 μM, a supplementation with glutathione (GSH, 350 μg/ml) was carried out to assess whether GSH may have a modulating effect on the Comet response. The effect of a fixed dose of BT was also evaluated in the presence of the exogenous antioxidant vitamin C (40 and 200 μM). Additionally, we investigated whether the polymorphism of glutathione S-transferase T1 ( GSTT1 ) gene may affect the individual level of BT-induced DNA damage in vitro . For all donors included in the present study, BT produced a significant dose-response relationship. No clear effect of GSH preincubation was seen on the BT-induced response. On the contrary, a significant reduction of DNA damage was observed in the presence of vitamin C (at least at 200 μM). Although our data suggest some individual differences according to the GSTT1 genotype in the outcome of the Comet assay, a large number of individuals should be studied in further investigations to obtain reliable conclusions.